Anticipatory climate governance in Central America - Veeger, Marieke; Muiderman, Karlijn; Vervoort, Joost M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Anticipating the possible impacts of climate change has become a key global focus. Scenarios and many other methods and tools are used today to imagine climate futures and develop strategies for realizing new futures while governing climate change. With the proliferation of these processes in sustainability-related research and planning contexts, scrutiny of their role in steering decision-making becomes increasingly important. How can the benefits and challenges of these processes of anticipation be better understood as governance interventions? Research into anticipatory climate governance processes in the Global South has remained very limited, while these regions are most vulnerable to climate change. This report therefore examines processes of anticipation in Central America. The research question we answer is: ‘through what approaches are diverse processes of anticipation used to govern climate change in diverse Central American contexts?’. In order to answer this question, we first examine what methods and tools are used to anticipate climate futures and their role in climate policy and decision-making. We then closely examine three case studies to understand their approaches to anticipatory governance. Additionally, we present the results of two regional meetings with stakeholders where we discussed the challenges that exist in each country to practice anticipatory climate governance and the opportunities to strengthen capacities in this field. Finally, we present recommendations for strengthening processes of anticipatory climate governance in the region.